Experimental studies to evaluate tensile and bond strength of Stainless-Steel Wire Mesh (SSWM) - P. V. Patel; D. D. Joshi; R. V. Makawana (Fracture and Structural Integrity)
Structural strengthening is vital to improve the load-carrying capacity of partially or severely damaged Reinforced Concrete (RC) elements. Fiber Reinforced Polymers (FRPs) are widely used for strengthening purposes. In this study, use of Stainless-Steel Wire Mesh (SSWM) is explored, as FRPs are having limitations like high cost, less fire resistance, and brittle behavior. The experimental studies are conducted to evaluate the mechanical properties of the SSWM, to explore its feasibility as a strengthening material. Three different variants of SSWM i.e., 3032, 4032 and 5034 are considered for the study. SSWM used in present study is a woven mesh made from stainless-steel wires manufactured in India. Important mechanical properties such as tensile strength and bond strength with concrete surface is experimentally evaluated in this study. Response of test specimens are evaluated with respect to ultimate load carrying capacity, corresponding deformations, rupture strain, and failure pattern. SSWM exhibits a tensile strength of 489.134-658.375 MPa which is comparable to tensile strength of various types of fibers used for strengthening. Based on experimental studies, it is found that SSWM 4032 performs better in different aspects, so it can be a good alternative for strengthening of RC elements compared to other FRP materials